INFLAMMATORY DENDRITIC CELLS IN THE HOST IMMUNE RESPONSE TO MYCOBACTERIA: THE ROLE OF CELLULAR METABOLISM - ELAYATI, KARIMA MOHAMED (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Mycobacterium tuberculosis (Mtb) causes an estimated 1.5 million deaths annually and BCG, the only available vaccine, is ineffective at preventing adult pulmonary TB. Inflammatory dendritic cells (DCs) play an essential role in both innate and adaptive immunity and are potential vaccine targets. A metabolic switch from oxidative phosphorylation to glycolysis occurs in murine inflammatory DCs stimulated with TLR agonists and is required for optimal activation. Glycolysis is the process of degradation of glucose which occurs in both anaerobic cellular respiration and aerobic respiration. It breaks glucose into pyruvate and energy is also released in the form of NADH and ATP. In the presence of oxygen, pyruvate can enter the TCA cycle to generate macromolecules and energy via mitochondrial respiration or, under anaerobic conditions, can be fermented to lactate and secreted by the cell. Activated immune cells often undergo aerobic glycolysis, where pyruvate is converted to lactate in the presence of oxygen, similar to the Warburg effect in cancer cells. This thesis explores the role of metabolism in the maturation and survival of human monocyte-derived dendritic cells (moDCs) infected by BCG. First, the role of glycolysis in the maturation and viability of BCG-infected moDCs was investigated. The DCs were infected with different amounts of GFP-tagged BCG or treated with the TLR4 agonist LPS in the presence of the glycolysis inhibitor 2-deoxy glucose (2DG). The impact of glycolysis inhibition on the upregulation and secretion of inflammatory cytokines, expression of cell surface maturation markers and viability was assessed. Phenotyping of mo-DCs as well as cell death assessment via Annexin/7AAD assays was carried out by flow cytometry. In cell-free supernatants, cytokine secretion was evaluated with the help of multiplex ELISA and expression of cytokine genes in cell lysates was determined by quantitative RT-PCR. Glycolysis was necessary for optimal CD86 cell surface expression, IL1β and IL-10 mRNA expression and IL-13 secretion by BCG-infected moDCs. Furthermore, glycolysis had a role in promoting BCG-induced necrosis, suggesting that it is not the main route of energy generation in this setting. Other parameters also related to maturation, including CCR7 and HLA-DR cell surface expression, were unaffected by 2DG. Second, metabolic flux of moDCs at rest and following infection with BCG at different multiplicities of infection and various time points after infection was measured via the Seahorse Metabolic Flux Analyser. Infection of moDCs with BCG resulted in increased flux through glycolysis under stressed conditions but minimal changes in basal rates of glycolysis. In addition, the effects of BCG on moDC metabolic flux were compared to those of the virulent H37Rv strain of Mtb. Infection with Mtb shows reduced mitochondrial respiration levels, which may reflect mitochondrial damage during Mtb infection. The glycolytic rate of infected moDCs could be increased by treatment with IFNγ and the anti-diabetes drug metformin, raising the possibility that metabolism could be manipulated to alter the immunogenicity of the BCG vaccine. Third, the Nanostring nCounter platform was utilized in order to measure the mRNA level of 180 genes involved in cellular metabolism in live and killed BCG-infected moDCs. Nanostring analysis revealed that infection with killed or live BCG stimulates the downregulation and upregulation of various metabolic genes in moDCs. Subsequent metabolic flux analysis utilizing metabolic modulators showed that BCG-infected moDCs increase their dependency on fatty acid oxidation compared to uninfected cells. This is the first report investigating the role of cellular metabolism in human DCs infected with mycobacteria. Overall, the results suggest that glycolysis plays an important though limited role in maturation of human moDCs after BCG infection and that mitochondrial respiration is maintained via fatty acid oxidation. Further investigation will be needed to determine whether manipulation of DC metabolism could enhance the protective effects of the BCG vaccine.
APPROVED
Keywords: TB - moDCs